Penyusunan Strategi Bisnis Menurut Perspektif Ekonomi Islam - Wati, Lisna (Yayasan Rahmat Islamiyah, 2024)
Islamic business strategy is becoming an increasingly interesting topic for practitioners and academics. In this article we explain business strategy, the concept of Islamic business principles and strategies based on the teachings of the Al-Quran and As-Sunnah. The method used is library research. Apart from that, this article will explain how determining an Islamic business strategy can improve company performance and benefit society as a whole. In short, business strategy can be a good alternative for business management because it provides a strong ethical foundation and promotes greater economic sustainability. The strategic plan of an organization/company is not only for get success in the world (worldly profits) but also profits in the afterlife (ukhrawi benefits) and gain the pleasure of Allah SWT.Â